Digitalization on Cocurricular System - Musthafa, Amirul Hafiz (IRC, 2020)
In this era of technology, digitalization offers new opportunities and benefits when create new products and services. Compared to 20th centuries, the world right now changing from traditional method to digital technology. Various tasks can be ease by using digital technology such as computer, applications, internet, handphone and many more. With this technology, people can do their work from anywhere, anytime, quicker, efficient and save cost. Nowadays, there are a lot of software and applications that exist in the internet that can use to solve various problems. This project is about using a newest and advance application in the internet for helping an organization that still using traditional method for filling system.